Method for detecting whether article contains plastic recycled material or not and method for semi-quantifying content of plastic recycled material in article

By combining lamp source and thermogravimetric analysis technology, the yellowing state and surface image defect state of the item are observed, and the content of recycled PET is detected by fluorescence spectroscopy, which solves the problem of difficult to quickly and accurately detect plastic recycling materials in the prior art, and achieves efficient and accurate detection results.

CN119827428APending Publication Date: 2025-04-15SGS TAIWAN LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411395438.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-10-13
Filing Date
2024-10-08
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

The prior art is difficult to quickly and accurately detect whether an article contains plastic recycled materials and its content ratio, especially in ensuring consistency in the quality of each batch of products.

Method used

By combining the first lamp source, the second lamp source and the thermogravimetric analysis device, the yellowing state, the surface image defect state and the activation energy value of the item are observed, and compared with the standard items to determine whether plastic recycling materials are contained. At the same time, the content of recovered PET was detected by fluorescence spectroscopy.

Benefits of technology

It realizes rapid and accurate detection of whether the article contains plastic recycling materials, and can semi-quantitatively determine its content ratio, solving the problems of detection difficulties and inconsistencies in the prior art.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119827428A_ABST
    Figure CN119827428A_ABST
Patent Text Reader

Abstract

The invention relates to a method for detecting whether an article contains a plastic recycled material and a method for semi-quantifying the content of the plastic recycled material of the article, which comprises the following steps: observing the yellowing state of the article through a first light source, irradiating the article through a second light source, and observing the defect number of an image on the surface of the article through an image capturing device. And acquiring an activation energy value of the article by using a thermogravimetric analysis device, and judging that the article contains the plastic recycled material when the yellowing index of the article is smaller than the standard yellowing index of the standard article, the second defect state is greater than the first defect state and the activation energy value is smaller than the standard activation energy value of the standard article. Moreover, the spectrogram of the recycled PET is different from that of the original PET, so that whether the recycled PET is contained in the detected article or not can be judged according to the spectrogram obtained through fluorescence spectrum analysis, and the content proportion of the recycled PET in the detected article can be judged according to the difference proportion between the spectrograms.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a method, in particular to a method for detecting whether an article contains plastic recycled materials and a method for qualitatively and semi-quantitatively determining the plastic recycled material content of an article. Background Art

[0002] With the continuous development of chemical and chemical technology, chemical products are increasingly used in people's lives. As a commonly used chemical product, plastics have become an indispensable part of people's daily lives. The development of plastic technology has enriched its variety, diversified its performance, and improved its functional characteristics.

[0003] However, due to the rising global trend of environmental protection and pollution prevention, many governments have begun to require public institutions and businesses to use recycled plastic products (i.e. recycled materials). In addition, major international brands have also set goals for using recycled materials. These measures have promoted the development of plastic recycling technology.

[0004] The above-mentioned recycled plastics include regenerated materials, recycled modified materials, and waste plastics. Regenerated materials are not necessarily waste plastics. The main differences between recycled materials and waste plastics are: (i) whether they are reprocessed by melt granulation or other processes in the factory production line, and (ii) whether their main plastic components are single or composite, while waste plastics are only simply cleaned and shredded, and the composition is relatively complex, often containing a variety of plastic components. Regenerated materials here refer to recycled and reused plastic materials, which are formed after proper treatment and processing. Such recycled materials usually come from the recycling and regeneration of plastic products, such as discarded plastic containers, packaging materials, plastic products, etc.

[0005] However, different recycled materials may have some safety concerns. This is because different recycled materials may come from different recycling sources, such as different types of waste plastic products and different recycling processes. In addition, there may be contaminants in the recycled materials, and these contaminants may come from the components of waste plastic products.

[0006] Moreover, there is another uncertain factor about recycled materials. These recycled materials are usually not properly stored and are often seen outdoors, exposed to wind, sun and rain, which makes the recycled materials more brittle.

[0007] The more recycled materials are added to the product, the more serious the plastic degradation may be, which in turn reduces the original structural strength of the plastic and makes it more prone to brittle cracking, especially in places that must withstand stress.

[0008] Therefore, before using recycled materials, it is necessary to carefully consider whether the quality and performance of the recycled materials can meet the requirements of specific applications, and conduct corresponding tests and verifications. Furthermore, it is necessary to conduct appropriate analysis and testing on the products that use recycled materials to ensure that the use of recycled materials complies with relevant regulations and standards.

[0009] Although manufacturers currently use third-party notarization agencies to confirm whether recycled materials are used in their products and the proportion of recycled materials added to the products through audits, this method can only certify the proportion of recycled materials added to the product at the time and in the current batch.

[0010] However, the above-mentioned audit and certification methods still cannot guarantee that the manufacturer adds recycled materials in each batch according to the declared proportion, so consumers or users have no way of knowing whether the products they use actually contain recycled materials and the relevant proportion of recycled materials added. It may be challenging to provide accurate verification of the content of recycled materials in plastics.

[0011] Therefore, it is a problem that those skilled in the art would like to solve to provide a detection method that can quickly confirm whether a product contains recycled materials and further confirm the approximate usage ratio of the recycled materials added to the product. Summary of the invention

[0012] One purpose of the present invention is to provide a method for detecting whether an article contains recycled plastic materials, wherein the yellowing state of the article is observed through a first light source, and the article is irradiated with a second light source, and the defect state of the image on the surface of the article is observed by an image capture device, and then a thermogravimetric analysis device is used to analyze and calculate the activation energy value of the article based on the thermogravimetric change of the article. Through the yellowing state of the article, the surface image and the activation energy value, it is determined whether the article contains recycled plastic materials. The method of the present invention is a qualitative detection method for quickly determining whether an article contains recycled plastic materials.

[0013] In view of the above-mentioned purpose, the present invention provides a method for detecting whether an article contains recycled plastic materials, which takes a first detection part, a second detection part and a third detection part of an article for detection, and the steps include detecting a basic yellowing index of the first detection part through a color difference measurement device, irradiating the first detection part with a first light source; after obtaining a yellowing index by detecting the first detection part through the color difference measurement device, a yellowing index of the first detection part is obtained according to the yellowing index and the basic yellowing index; capturing a first surface image of the second detection part through an image capture device, spraying a water mist on the second detection part within a total detection time, irradiating a second light source, and capturing the second detection part through the image capture device. a second surface image of the detection part, taking the third detection part and placing it in a detection chamber of a thermogravimetric analysis device, and causing the third detection part to produce a thermogravimetric change in the detection chamber, the thermogravimetric analysis device analyzes and calculates according to the thermogravimetric change, obtains an activation energy value, compares the yellowing index with a standard yellowing index of a standard article, a first defect state of the first surface image and a second defect state of the second surface image, and the activation energy value with a standard activation energy value of a standard article, wherein when the yellowing index is less than the standard yellowing index, the second defect state is greater than the first defect state, and the activation energy value is less than the standard activation energy value, it is determined that the article contains the plastic recycled material of the plastic material portion.

[0014] The present invention provides an embodiment, wherein in the step of irradiating the first detection portion with a first light source, the first light source uses a UV light source, a xenon arc light source, a carbon arc light source or a mercury lamp source.

[0015] The present invention provides an embodiment, wherein the UV light source is between 200nm and 400nm.

[0016] The present invention provides an embodiment, wherein before the step of detecting a basic yellowing index of the first detection part through a color difference measuring device, the steps include: taking a standard object and using the color difference measuring device to detect and obtain a first yellowing index; after irradiating the standard object with the first light source, using the color difference measuring device to detect and obtain a second yellowing index of the standard object; obtaining a standard yellowing index according to the second yellowing index and the first yellowing index, wherein the standard object is an object that does not contain recycled plastic material

[0017] The present invention provides an embodiment, wherein the step of irradiating the first detection portion with a first light source includes the step of: the first light source irradiates the first detection portion according to an irradiation time, wherein the irradiation time is between 24 hours and 450 hours.

[0018] The present invention provides an embodiment, wherein within a total detection time, after spraying water on the second detection part, in the step of irradiating a second light source, the second light source uses a UV light source, a xenon arc light source, a carbon arc light source or a mercury lamp source.

[0019] The present invention provides an embodiment, in which the step of irradiating a second light source after spraying water on the second detection part within a total detection time includes the steps of: within a first time interval, using the second light source to irradiate a surface of the second detection part, wherein the surface has a first temperature, and the first temperature is between 50 and 80° C., within a second time interval, spraying the water mist to the second detection part, and simultaneously using the second light source to irradiate the second detection part, wherein the second light source is in an off state when spraying the water, and wherein the first time interval and the second time interval are repeatedly executed in a cycle during the total detection time.

[0020] The present invention provides an embodiment, wherein in the step of using the second light source to illuminate the second detection portion within a first time interval, the first time is between 85 and 150 minutes.

[0021] The present invention provides an embodiment, wherein in the step of spraying the water mist onto the second detection portion and then irradiating the second light source within a second time interval, the second time is between 5 and 60 minutes.

[0022] The present invention provides an embodiment, wherein before the step of placing the third detection part in a detection chamber of a thermogravimetric analysis device and causing the third detection part to produce a thermogravimetric change in the detection chamber, the steps include: placing a standard object in the detection chamber, and adjusting a chamber temperature of the detection chamber to cause the standard object to produce a standard thermogravimetric change in the detection chamber; and the thermogravimetric analysis device analyzes and calculates according to the standard thermogravimetric change to obtain a standard activation energy value; wherein the chamber temperature is between 20 and 1000°C.

[0023] The present invention provides an embodiment, wherein the step of obtaining an activation energy value by analyzing and calculating the thermogravimetric change by the thermogravimetric analysis device includes the step of adjusting a chamber temperature of the detection chamber, wherein the chamber temperature is between 20 and 1000° C., and the thermogravimetric analysis device obtains the thermogravimetric change of the third detection portion by a temperature change of the chamber temperature.

[0024] The present invention provides an embodiment, wherein the article is composed of the plastic recycled material and / or a non-plastic recycled material, and further, the plastic recycled material and the non-plastic recycled material are selected from one of polyethylene, polypropylene, polyethylene terephthalate, polycarbonate, polycarbonate and acrylonitrile butadiene styrene copolymer, polystyrene or thermoplastic polyurethane.

[0025] In addition, given that environmental regulations in various countries have declared a target of 25% for the use of recycled plastics in non-food grade plastic containers, testing the proportion of recycled materials added to plastic containers is an important measurement method.

[0026] It has been shown that the threshold aggregation concentrations in both fluorescent and nonfluorescing dye-polymer systems depend on the crystallinity of the polymer host, the relative dye (guest) solubility, and the number of dye-polymer (guest-host) interactions.

[0027] To this end, the present invention utilizes the difference in bonding and crystallinity between the molecules of a single component or a composite component of a mixed plastic matrix formed by the reprocessing process of melt granulation using virgin plastic and added recycled plastic in the plastic manufacturing process, and uses an alkaline solution for extraction and detection. The alkaline solution will weaken the bonding of the added recycled plastic and make it free. Then, by utilizing the difference in bonding strength, the fluorophore is dispersed in a continuous matrix. When the concentration of the fluorescent dye increases, its formation energy aggregates with the detached recycled plastic molecular groups, and the difference in the strength of the scattered wave between the virgin plastic and the recycled plastic can be seen on the double frequency wave of the excitation light source. The present invention can be used to quickly determine whether an article contains recycled plastic and the relevant proportion of the recycled plastic added.

[0028] Another object of the present invention is to provide a method for detecting whether an article contains recycled plastic materials and a method for semi-quantitatively determining the recycled plastic material content of an article, by using a spectrum obtained by fluorescence spectral analysis to determine whether the article contains recycled PET and to determine the content ratio of recycled PET in the article.

[0029] In view of the above-mentioned purpose, the present invention provides a method for detecting whether an article contains recycled plastic materials, the steps of which include: taking a test article (pre-processed in advance, the test article is first cut into 1 cm x 1 cm size) and adding it to a glass beaker; taking a sodium hydroxide solution and adding it to the glass beaker, covering it with a watch glass cover and performing an extraction treatment (the extraction treatment temperature is between 105° C. and 125° C., and the extraction treatment time is between 70 and 100 minutes) to form an extraction sample; taking deionized water to wash the glass beaker and the extraction sample on the watch glass cover to form an extraction liquid; taking the extraction liquid and a PET sample solution and adding a 4,4,-bis(2-benzoxazolyl) to each other, and then performing a fluorescence analysis under an analytical condition. Spectral analysis (using a fluorescence spectrometer to detect and observe the intensity of the double-frequency wave indicating the amount of polymer bond loss, and observing the signal intensity through the double-frequency wave signal intensity) is performed to obtain a detection spectrum and a PET original spectrum; the detection spectrum and the PET original spectrum are analyzed and compared; and when the detection spectrum is not equal to the PET original spectrum, it is determined that the detection article contains a recovered PET (observing through the double-frequency wave signal intensity that the signal intensity of the extraction liquid is greater than the signal intensity of the PET sample solution and also greater than the signal intensity of the blank group solution).

[0030] The present invention provides an embodiment, wherein the analysis conditions are as follows: the excitation wavelength is set at 373 nm, the incident slit is set at 5 nm, the emission slit is set at 5 nm, the wavelength scanning range is set between 360 nm and 800 nm, and the scanning rate is within 120 nm / min.

[0031] The present invention provides an embodiment (another determination method), wherein after the step of taking deionized water to rinse the extraction sample on the glass beaker and the watch glass cover to form an extraction liquid, the method further comprises the steps of: filtering the extraction liquid to form a test sample; performing a drying treatment on the test sample and a PET original sample respectively (the drying treatment temperature is between 90° C. and 120° C., and the drying treatment time is between 6 and 9 hours), respectively recording a test color of the test sample and a PET color of the PET original sample; and comparing the test color with the PET color. When the test color is different from the PET color, it is determined that the test object contains a recycled PET.

[0032] In view of the above-mentioned purpose, the present invention further provides a method for semi-quantitatively determining the content of recycled plastic materials in an article, the steps of which include: taking a test article (pre-processed in advance, wherein the test article is first cut into 1 cm x 1 cm size) and adding it to a glass beaker; taking a sodium hydroxide solution and adding it to the glass beaker, covering it with a watch glass cover and performing an extraction treatment (the temperature of the extraction treatment is between 105° C. and 125° C., and the time of the extraction treatment is between 70 and 100 minutes) to form an extraction sample; taking deionized water to rinse the glass beaker and the extraction sample on the watch glass cover to form an extraction liquid; taking the extraction liquid and a PET sample solution and adding 4,4-bis(2-benzoxazolyl) respectively, and performing a fluorescence spectrum analysis under an analytical condition to obtain a test spectrum and a PET original spectrum; analyzing and comparing the test spectrum and the PET original spectrum; and analyzing and obtaining the content ratio of the recycled PET in the test article according to the difference ratio between the test spectrum and the PET original spectrum.

[0033] The present invention provides an embodiment, wherein the analysis conditions are as follows: the excitation wavelength is set at 373 nm, the incident slit is set at 5 nm, the emission slit is set at 5 nm, the wavelength scanning range is set between 360 nm and 800 nm, and the scanning rate is within 120 nm / min. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1A :It is a schematic diagram of a process of an embodiment of the present invention; Figure 1B :It is a schematic diagram of a process of an embodiment of the present invention; Figure 1C : It is a schematic diagram of cutting out the same sample of the first detection part, the second detection part and the third detection part according to an embodiment of the present invention; Figure 1D :It is a schematic diagram of the process of the standard yellowing index according to one embodiment of the present invention; Figure 1E :It is a schematic diagram of the process of the first light source of one embodiment of the present invention; Figure 1F :It is a schematic diagram of the process of the second light source of one embodiment of the present invention; Figure 1G :It is a schematic diagram of the process of the standard activation energy value of one embodiment of the present invention; Figure 1H :It is a schematic diagram of a process of an embodiment of the present invention; Figure 2A : It is a schematic diagram of image capture according to an embodiment of the present invention; Figure 2B:It is a schematic diagram of a first image and a second image containing recycled plastic material according to an embodiment of the present invention; Figure 2C : It is a schematic diagram of a first image and a second image that do not contain recycled plastic materials according to an embodiment of the present invention; Figure 3 : It is a schematic diagram of the activation energy value of one embodiment of the present invention; Figure 4 :It is a schematic diagram of a flow chart of another embodiment of the present invention; and Figure 5A-Figure 5C : It is a comparative spectrum overlay of another embodiment of the present invention.

Figure number comparison

[0035] In order to further understand and appreciate the structural features and effects of the present invention, a preferred embodiment and detailed description are provided as follows:

[0036] It is known that manufacturers rely on third-party notarization units to add recycled plastic materials, use the total amount of recycled plastic materials for physical audits, and use this method to certify the proportion of recycled plastic materials added to the product. However, although this method can certify the proportion of recycled plastic materials added to the product, it cannot guarantee that the manufacturer adds and produces each batch according to the declared ratio of recycled plastic materials to non-plastic recycled materials. Therefore, stakeholders have no way of knowing whether the product really contains recycled materials.

[0037] The present invention observes the yellowing state, surface image and activation energy value of the object through the first light source, the second light source and the thermogravimetric analysis device, and confirms whether the object made by the manufacturer adds plastic recycled materials in the object or product through the yellowing state, surface image and activation energy value of the object.

[0038] Hereinafter, the present invention will be described in detail by illustrating various embodiments of the present invention with reference to the drawings. However, the concept of the present invention may be embodied in many different forms and should not be construed as being limited to the exemplary embodiments described herein.

[0039] First, see Figure 1B , which is a flow chart of an embodiment of the present invention. As shown in the figure, the method of detecting whether an article contains plastic recycling materials in this embodiment comprises the following steps:

[0040] Step S5: Detecting the basic yellowing index of the first detection part through a color difference measuring device;

[0041] Step S10: irradiating the first detection portion with a first light source;

[0042] Step S20: Detecting the first detection part by using a color difference measuring device to obtain a yellowing index, and obtaining a yellowing index of the first detection part according to the yellowing index and the basic yellowing index;

[0043] Step S30: capturing a first surface image of the second detection portion through an image capture device;

[0044] Step S40: After spraying water mist on the second detection part within a total detection time, irradiate the second light source;

[0045] Step S50: capturing a second surface image of the second detection portion through an image capture device;

[0046] Step S60: placing the third detection part in the detection chamber of the thermogravimetric analysis device, and causing the third detection part to produce thermogravimetric changes in the detection chamber;

[0047] Step S70: The thermogravimetric analysis device analyzes and calculates according to the thermogravimetric changes to obtain the activation energy value; and

[0048] Step S80 : comparing the yellowing index with the standard yellowing index, the first defect state of the first surface image with the second defect state of the second surface image, and the activation energy value with the standard activation energy value.

[0049] Among them, please refer to Figure 1AThe operation flow of this embodiment is a flow chart of one embodiment of the present invention. As shown in the figure, in the method of detecting the plastic recycled material composition of an article of this embodiment, step S5, step S10 to step S20 are aging tests using the first light source, step S30, step S40 to step S50 are experiments using the second light source to simulate sunlight, and step S60 to step S70 are thermogravimetric analysis tests. In this process, the order of aging tests using the first light source, experiments using the second light source to simulate sunlight, and thermogravimetric analysis tests is not fixed and can be replaced according to the experimental requirements (not limited to Figure 1B process).

[0050] In this embodiment, please refer to Figure 1C , which is a schematic diagram of a first detection unit, a second detection unit and a third detection unit according to an embodiment of the present invention, as shown Figure 1C As shown, an object 10 includes a first detection portion 12, a second detection portion 14 and a third detection portion 16. The first detection portion 12, the second detection portion 14 and the third detection portion 16 can be divided into three parts from a single object 10 for subsequent detection. Figure 1C , the object 10 was cut into three detection parts in the same way as cutting a cake for experiment.

[0051] The article 10 used in this embodiment is composed of the plastic recycled material and / or a non-plastic recycled material, wherein the aforementioned plastic recycled material and the non-plastic recycled material are selected from one of polyethylene, polypropylene, polyethylene terephthalate, polycarbonate, polycarbonate, polycarbonate and acrylonitrile butadiene styrene copolymer, polystyrene or thermoplastic polyurethane.

[0052] Wherein, before step S5, the following steps are included:

[0053] Step S1: Take a standard object and use a color difference measuring device to measure and obtain a first yellowing index;

[0054] Step S2: irradiating the standard object with a first light source, and detecting and obtaining a second yellowing index of the standard object by a color difference measuring device;

[0055] Step S3: Obtaining a standard yellowing index according to the second yellowing index and the first yellowing index.

[0056] Before the UV aging test begins, a standard article (not shown) is first taken. The standard article is the same as the article 10, wherein the standard article is an article that does not contain recycled plastic material.

[0057] In step S1 to step S3, the standard article is firstly taken and detected by the color difference measuring device to obtain a first yellowing index, and then the standard article is irradiated with the first light source, and then the color difference measuring device is used to detect and obtain a second yellowing index of the standard article, and finally a standard yellowing index is obtained according to the difference between the second yellowing index and the first yellowing index.

[0058] Next, after obtaining the standard yellowing index, please refer to Figure 1A or Figure 1B As described in step S5, step S10 to step S20, it is an aging test of the first light source of this embodiment. A basic yellowing index of the first detection part 12 is detected through a color difference measurement device, and the first detection part 12 is irradiated with a first light source to perform an aging test.

[0059] The first lamp used in the above embodiments is a UV lamp, a xenon arc lamp, a carbon arc lamp or a mercury lamp. If the first lamp is the UV lamp, the wavelength of the UV lamp is between 200nm and 400nm.

[0060] In this embodiment, please refer to Figure 1E , which is a schematic diagram of the process of the first light source of an embodiment of the present invention. As shown in the figure, after step S10, the following steps are included:

[0061] Step S11: The first light source illuminates the first detection portion according to the illumination time.

[0062] In this embodiment, the first detection portion 12 is irradiated with the first light source, and a yellowing index of the first detection portion is obtained according to the yellowing index and the basic yellowing index.

[0063] The color difference measuring device is a precision optical instrument that measures color differences based on the principle of light and electrical conversion. It is a color identification instrument designed based on the principle of a spectrophotometer. The color difference measuring device can measure the color value of a sample to identify the position of the color of the object 10 in a color space. By comparing the object 10 with a standard color sample, the difference between the object 10 and the standard color sample is obtained. The color difference measuring device is widely used in industries such as metals, ceramics, plastics, coatings, textiles, printing and chemicals.

[0064] Next, refer to Figure 1A or Figure 1BAs described in step S30 to step S50, before the detection, a first surface image 141 of the second detection part 14 is captured by an image capture device (not shown in the figure). After the first surface image 141 is captured, a water mist is sprayed on the surface of the second detection part 14 within a total detection time, and then a second light source is irradiated, wherein the second light source is the UV light source, the xenon arc light source, the carbon arc light source or the mercury lamp source. If the second light source is the UV light source, the wavelength of the UV light source is between 200nm and 400nm.

[0065] Please also refer to Figure 1F , which is a schematic diagram of the process of the second light source of an embodiment of the present invention. As shown in the figure, in step S40, the steps are further included:

[0066] Step S41: using a second light source to illuminate the surface of the second detection portion within a first time interval; and

[0067] Step S42: spraying water mist onto the second detection portion within the second time interval.

[0068] In step S41 of this embodiment, the second detection unit 14 first uses the second light source to illuminate a surface thereof within a first time interval, wherein the xenon arc lamp heats up the surface, so that the surface has a first temperature between 50 and 80°C.

[0069] Then in step S42, the water is sprayed on the second detection part within a second time interval, wherein the second light source is turned off when the water mist is sprayed, and the first time interval and the second time interval are repeatedly executed in the total detection time. In this embodiment, after repeating the above two time intervals, the image capture device is used to capture a second surface image 142 of the second detection part 14.

[0070] Among them, please refer to Figure 2A , which is a schematic diagram of image capture according to an embodiment of the present invention, Figure 2A As shown, the first surface image 141 and the second surface image 142 are obtained by marking a central observation point C1 on the surface before the second detection unit 14, and then focusing on the central observation point C1 using the image capture device. With the central observation point C1 as the center, a first image M1 is obtained upward, a second image M2 is obtained downward, a third image M3 is obtained on the left, and a fourth image M4 is obtained on the right.

[0071] Among them, the second light source described in this embodiment is an artificial climate simulation test that simulates natural sunlight, which is usually used for accelerated tests of the photostability and weather resistance of various materials or products. It is known that this method is used as a test for screening new materials, improving existing materials, or evaluating the durability of material components after changes.

[0072] Next, refer to Figure 1A and Figure 1B In the contents of step S60 and step S70, the third detection part 16 is placed in a detection chamber of a thermogravimetric analysis device, and the third detection part 16 produces a thermogravimetric change in the detection chamber. The thermogravimetric analysis device analyzes and calculates according to the thermogravimetric change to obtain an activation energy value.

[0073] Among them, please refer to Figure 1G , which is a schematic flow diagram of the standard activation energy value of an embodiment of the present invention. As shown in the figure, before step S60, the steps include:

[0074] Step S61: placing a standard object in a testing chamber, and adjusting the chamber temperature of the testing chamber to cause a standard thermogravimetric change to be generated by the standard object in the testing chamber; and

[0075] Step S62: The thermogravimetric analysis device performs analysis and calculation based on the standard thermogravimetric change to obtain a standard activation energy value.

[0076] In this embodiment, the standard object is placed in the detection chamber, and a chamber temperature of the detection chamber is adjusted to make the standard object produce a standard thermogravimetric change in the detection chamber. The thermogravimetric analysis device analyzes and calculates according to the standard thermogravimetric change to obtain a standard activation energy value, wherein the chamber temperature is between 20 and 1000°C.

[0077] Next, when conducting the thermogravimetric analysis experiment of the third detection unit 16, please refer to Figure 1H , which is a flow chart of an embodiment of the present invention. As shown in the figure, in step S70, the steps are included:

[0078] Step S71: adjusting the chamber temperature of the detection chamber; and

[0079] Step S72: The thermogravimetric analysis device obtains the thermogravimetric change of the third detection part according to the temperature change of the chamber temperature.

[0080] In this embodiment, after the third detection part 16 is placed in the detection chamber of the thermogravimetric analysis device, the chamber temperature is adjusted. Here, the chamber temperature is adjusted to a temperature change, which gradually increases the temperature with a temperature gradient, or / and performs detection of the third detection part through repeated cycles of heating and cooling. After the detection is completed, the thermogravimetric change of the third detection part generated during the temperature change is obtained.

[0081] In this embodiment, the activation energy value of the third detection portion 16 is obtained by analyzing and calculating the thermogravimetric change using the thermogravimetric analysis device.

[0082] In this embodiment, the thermogravimetric analysis device is used to control the sample under a certain temperature process (increase / decrease / constant temperature), observe the change process of the sample mass with temperature or time, obtain relevant information such as weight loss ratio, weight loss temperature, and decomposition residue, and calculate the weight loss rate at each temperature based on the slope of each point on the weight loss curve, so as to calculate the decomposition rate constant and reaction activation energy of the third detection unit 16.

[0083] This embodiment uses the Arrhenius equation, that is, Formula 1, to perform calculations (the Arrhenius equation is mainly based on k(T), that is, the change in the rate constant)

[0084] Through the Arenis equation, the reaction rate can be logarithmized to obtain an XY format curve. By referring to the algorithm disclosed in ASTM (the standard of the American Society for Testing and Materials International Organization), multiple different reaction rate calculations are performed, and the activation energy value (Ea) of the object 10 and the standard activation energy value (Ea) of the standard object can be obtained during the experiment.

[0085] Finally, in the content described in step S80, the difference between the yellowing index and a standard yellowing index, the defect quantity of a first defect state of the first surface image and a second defect state of the second surface image, and the activation energy value and the standard activation energy value are compared. When the yellowing index is less than the standard yellowing index, the defect quantity of the second defect state is greater than the defect quantity of the first defect state, and the activation energy value is less than the standard activation energy value, it is determined that the article contains part of the plastic recycled material.

[0086] That is to say, when a user obtains the article 10 (which can be a single or multiple items), the manufacturer that provides the article 10 will also provide the standard article, which is the article that does not contain recycled plastic materials. Before the article 10 is tested, it is first tested to obtain the standard yellowing index and the standard activation energy value.

[0087] Next, the user takes out the first detection part 12, the second detection part 14 and the third detection part 16 from the article 10, and performs the irradiation experiment of the first light source, the irradiation experiment of the second light source and the experiment of the thermogravimetric analysis device, and obtains the yellowing state, surface image and the activation energy value of the article 10, and determines whether the article 10 contains plastic recycled materials by using the three data and the standard yellowing index and the standard activation energy value of the standard article.

[0088] The advantage of this embodiment is that by simultaneously performing the irradiation experiment of the first light source, the irradiation experiment of the second light source and the experiment of the thermogravimetric analysis device, the yellowing state of the object 10, the surface image of the object 10 and the activation energy value of the object 10 can be obtained, so as to quickly determine whether the object 10 contains plastic recycled materials.

[0089] Next, the article 10 is PET as an implementation example. First, a PET (the article 10) is split into the first detection step 12, the second detection part 14 and the third detection part 16. The conditions for performing experiments 1, 2 and 3 are as follows:

[0090] 1. Experiment 1: Refer to the test method of ASTM-American Society for Testing and Materials International to adjust the experimental parameters and conduct the experiment:

[0091] Lamp used: UV Lamp (the first light source);

[0092] Irradiation energy: 0.3~1.5W / m 2 ;

[0093] Each cycle condition: continuous illumination, blackboard temperature 50°C-80°C (the first temperature); and

[0094] Continuous illumination time: 24 to 450 hours.

[0095] After the irradiation, the color difference measuring device (Spectrophotomete, r / MINOLTA) was used for measurement. The measuring conditions were as follows: light source: CIE illuminant D65, standard viewing angle: CIE 1964 standard observer, measuring aperture: ψ25.4 mm, measuring interval: 10 nm, wavelength range: 360 nm to 740 nm, and measuring mode: through-type measurement. The experimental results are shown in Table 1 below. Table 1 is a comparison table of the yellowing index of the article and the standard yellowing index of the standard article. Table 1 Comparison table of the article and the standard article (After lighting) Difference (After lighting) Difference 0.33 1.56 1.23 0.26 1.89 1.63

[0096] Among them, the standard yellowing index of the standard article and the yellowing index of the article 10 include the difference in yellowing chromaticity and the difference in yellowing index. In this experiment, it can be clearly seen from the results presented in the above Table 1 that the difference in yellowing chromaticity and the difference in yellowing index of the yellowing index of the article 10 are smaller than the difference in yellowing chromaticity and the difference in yellowing index of the standard yellowing index (the article not containing recycled plastic material). Therefore, the standard yellowing index of the standard article and the yellowing index of the article 10 can be compared by detecting the UV light source. When the difference in the yellowing index of the article 10 is smaller than the standard yellowing index, the article 10 can be judged as containing the plastic recycled material.

[0097] 2. Experiment 2: The second light source irradiation experiment was conducted by referring to the ISO (International Organization for Standardization) method and adjusting the experimental parameters, wherein the second light source of Experiment 2 used the xenon arc lamp source.

[0098] Lamp: xenon arc lamp (the second light source);

[0099] Filter: Daylight;

[0100] Irradiation energy: 0.3~1.5W / m 2 ;

[0101] Conditions for each cycle: 85-150 minutes of illumination, standard blackboard temperature;

[0102] 50-80±3℃, ambient temperature 38±3℃, relative humidity;

[0103] 50±10%RH; 18 minutes of lighting and humidification; and

[0104] Continuous illumination time: 24 to 450 hours.

[0105] Before the irradiation experiment of the xenon arc lamp source, the first surface image 141 of the second detection portion 14 is photographed by the image capture device (OLYMPUS Optical Microscope), and after the irradiation experiment of the xenon arc lamp source, the second surface image 142 is photographed.

[0106] Please refer to the image capture device for the method of capturing images. Figure 2A First, mark the central observation point C1 on the surface, adjust the image capture device to focus on the central observation point C1, and then, with the central observation point C1 as the center, obtain the first image M1 upward, the second image M2 downward, the third image M3 on the left, and the fourth image M4 on the right.

[0107] The first image M1 , the second image M2 , the third image M3 , and the fourth image M4 of the first surface image 141 and the first image M1 , the second image M2 , the third image M3 , and the fourth image M4 of the second surface image 142 are obtained respectively and compared.

[0108] The method for obtaining the first image M1, the second image M2, the third image M3 and the fourth image M4 of the surface image 141 of the standard object and the first image M1, the second image M2, the third image M3 and the fourth image M4 of the second surface image 142 is the same as described above and will not be repeated herein.

[0109] For comparison results, please refer to Figure 2B , which is a schematic diagram of a first image and a second image containing recycled plastic material according to an embodiment of the present invention. As shown in the figure, the image comparison result clearly shows that after the second detection unit 14 is irradiated by the xenon arc lamp source, the defect quantity of the second defect state (the second surface image 142) is much greater than the defect quantity of the first defect state (the first surface image 141).

[0110] The results of the first image 141 and the second image 142 of the standard object are shown in FIG. Figure 2C , which is a schematic diagram of a first image and a second image that do not contain recycled plastic materials according to an embodiment of the present invention. The image comparison result clearly shows that after the second detection unit 14 is irradiated by the xenon arc lamp source, the defect quantity of the second defect state is the same as the defect quantity of the first defect state. After being irradiated by the xenon arc lamp source, the defect quantity of the surface defect state of the standard object is not increased.

[0111] From the comparison result of the second detection part 14 of the article 10 and the standard article, the standard article is the article that does not contain the recycled plastic material. By comparing the experimental results, it can be confirmed that when the article 10 contains the recycled plastic material, more defects will appear on the surface after being irradiated by the xenon arc lamp source. If the article 10 is the article that does not contain the recycled plastic material, the number of defects on the surface will not increase too much before and after being irradiated by the xenon arc lamp source. Therefore, by comparing the number of defects, it can be confirmed whether the composition of the article 10 contains the recycled plastic material.

[0112] 3. Experiment 3: Adjust the experimental parameters with reference to the test method of ASTM (American Society for Testing and Materials) to conduct material kinetic activation energy analysis, and conduct thermogravimetric analysis experiments on the article 10 containing 0%, 10%, 50% and 100% of the recycled plastic material, wherein the article 10 containing 0% of the recycled plastic material is the standard article, and the remaining articles 10 containing 10%, 50% and 100% of the recycled plastic material are test articles. The standard activation energy value is obtained by using the standard article, and activation energy values ​​of various proportions are obtained according to the article 10 containing 10%, 50% and 100% of the recycled plastic material.

[0113] For the experimental results, please refer to Figure 3 , which is a schematic diagram of the activation energy value of an embodiment of the present invention, as shown in the figure, Figure 3 The results show that when the article 10 contains the recycled plastic material, its activation energy value is less than that of the standard article that does not contain the recycled plastic material. Therefore, when the activation energy value of the article 10 is less than the standard activation energy value of the standard article, it can be confirmed whether the composition of the article 10 contains the recycled plastic material.

[0114] Therefore, it can be known from the experimental results of Experiment 1, Experiment 2 and Experiment 3 that when the yellowing index difference of the article 10 is less than the standard yellowing index difference, the number of defects in the second defect state is greater than the number of defects in the first defect state, and the activation energy value is less than the standard activation energy value, it can be determined that the manufacturing formula of the plastic material of the article 10 contains part of the plastic recycled material.

[0115] The above-described embodiments of the present invention are a method for detecting whether an article contains recycled plastic materials. The method observes the yellowing state of the article through a first light source, irradiates the article with a second light source, and observes the defect state of the image on the surface of the article through an image capture device. Then, a thermogravimetric analysis device is used to analyze and calculate the activation energy value of the article based on the thermogravimetric change of the article. After comparing the yellowing state, surface image defect state and activation energy value of the article with the standard yellowing index, defect state and standard activation energy value of the standard article, it is determined whether the article contains recycled plastic materials based on the comparison result. Whether the article contains recycled plastic materials can be quickly determined by the method of the present invention.

[0116] For further information, see Figure 4 , which is a flow chart of another embodiment of the present invention, such as Figure 4 As shown, a method for detecting whether an article contains plastic recycled materials and a method for semi-quantitatively determining the plastic recycled material content of an article, the steps of which include:

[0117] Step S91: Put the test object into a glass beaker;

[0118] Step S92: adding sodium hydroxide solution into a glass beaker, covering it with a watch glass cover, and performing extraction treatment to form an extraction sample;

[0119] Step S93: taking deionized water to rinse the extraction sample on the glass beaker and the watch glass cover to form an extraction liquid;

[0120] Step S94: adding 4,4-bis(2-benzoxazolyl) to the extraction liquid and the PET sample solution respectively, and then performing fluorescence spectrum analysis under analysis conditions to obtain a detection spectrum and a PET original spectrum;

[0121] Step S95: Analyze and compare the detected spectrum and the PET original spectrum; and

[0122] Step S96: When the detected spectrum is not equal to the original PET spectrum, it is determined that the detected object contains recycled PET.

[0123] As shown in step S91, a test object (about 2.5 g) is added to a 200 mL glass beaker. Before being placed in the glass beaker, the test object is pre-processed. The pre-processing first cuts the test object into 15 cm x 15 cm pieces, and then cuts the test object (pieces) into 1 cm x 1 cm sizes.

[0124] As shown in step S92, 30 mL of a sodium hydroxide solution (10% NaOH) is added to the glass beaker (and a magnet is placed at the same time), covered with a watch glass cover, and placed on a temperature-controlled hot plate for an extraction process (wherein the extraction process temperature is between 105° C. and 125° C., and the extraction process time is between 70 and 100 minutes (preferably 90 minutes)) to form an extraction sample. When the extraction sample is completed, the glass beaker is removed from the hot plate and cooled for about 20 minutes.

[0125] Subsequently, as shown in step S93, 40 mL of deionized water is taken to rinse the glass beaker and the extraction sample on the watch glass cover (rinsing is performed in small amounts in batches) to form an extraction liquid.

[0126] Next, as shown in step SS94, 10 mL of the extraction liquid and 10 mL of a PET sample solution (100% PET virgin plastic obtained in steps S91 to S93) are taken respectively, and at the same time, 10 mL of a blank group solution (deionized water only), 10 mL of the 10% sodium hydroxide solution and 10 mL of a 100% recycled PET material solution (100% recycled PET (rPET) obtained in steps S91 to S93) are taken and placed in 25 mL clean glass test tubes with lids (at the same time, a small amount of the solution is taken into another plastic test tube).

[0127] Before performing a fluorescence spectrum analysis, each solution in another plastic test tube was observed, and it was found that the extraction liquid was slightly turbid and had poor light transmittance, while the PET sample solution was relatively clear and had good light transmittance.

[0128] Next, 2 mL of 4,4-bis(2-benzoxazolyl) (BBS, a fluorescent dye approved by the U.S. FDA for use in food / non-food contact products) was added to a 25 mL clean glass test tube with a lid, and then the mixture was transferred to a quartz cuvette. The fluorescence spectrum was analyzed under analytical conditions (the excitation wavelength was set at 373 nm, the incident slit was set at 5 nm, the emission slit was set at 5 nm, the wavelength scanning range was set from 360 nm to 800 nm, and the scanning rate was within 120 nm / min), and a detection spectrum (from the extraction liquid), a PET original spectrum (from the PET sample solution), a blank group spectrum (from the blank group solution), an alkaline solvent spectrum (from the sodium hydroxide solution), and an rPET spectrum (from the 100% recycled PET material solution) were obtained.

[0129] When performing the fluorescence spectrum analysis, the corresponding fluorescence spectra of each group (the extraction liquid, the PET sample solution, the blank group solution, the 10% sodium hydroxide solution and the 100% recovery type PET material solution) are recorded, and the instrument fluorescence intensity value at a wavelength of 445nm when excited with a wavelength of 373nm is read (for calculating the added 0.05% BBS concentration (QE quantitative value)), and the spectrum of the instrument fluorescence intensity value falling around the double frequency wave of the emission wavelength of 746nm is observed.

[0130] In the measurement of step S94, the fluorescence spectrum needs to be recorded when the instrument fluorescence intensity value at the wavelength of 445nm is read. If the wavelength position of the highest intensity of the emission spectrum deviates from 445nm, the excitation wavelength should be adjusted until the corresponding emission wavelength falls at 445nm, then the instrument fluorescence intensity value is read and the adjusted excitation wavelength is recorded.

[0131] It has been shown that the threshold aggregation concentrations in both fluorescent and nonfluorescing dye-polymer systems depend critically on the crystallinity of the polymer host, the relative dye (guest) solubility, and the number of dye-polymer (guest-host) interactions.

[0132] BBS dyes belong to this category of conjugated π-system fluorophores that are aggregation-induced enhanced emission (AIEE). When the fluorophores are dispersed in a continuous matrix and the concentration of the fluorescent dyes increases, their formation energy aggregates with the detached recycled plastic molecular groups, and aggregation color development occurs.

[0133] Therefore, by utilizing the aggregation-induced interaction between the BBS dye and the recycled PET molecules that have been detached and are free in the solution, after the excitation energy, the negative Coulomb coupling between the aggregated molecules reduces the energy of the first excited state, red-shifts and enhances the fluorescence emission, and the resulting aggregates can exhibit different photophysical properties relative to their monomeric counterparts.

[0134] At present, most of the manufacturing processes of recycled plastics are produced by the physical mixing method of virgin plastic and recycled PET (recycled polymer) in the reprocessing process of melt granulation. The single-component plastic matrix formed by the mixing process, or the recycled plastic with different composite components of the plastic matrix, has weaker intermolecular bonds and changed molecular crystallinity.

[0135] To this end, when an alkaline solution is used as a solvent for sample extraction and heated, the recycled plastics of a single component or different composite components are formed, and the bonds between the molecular structures are weakened and the crystallinity of the molecules is changed, making it easy for the molecules of the recycled PET in the recycled plastic to fall off and become free, and stably exist in the solution.

[0136] Therefore, when the test object contains a high proportion of recycled PET, after extraction, more molecular groups of the recycled PET will fall off and become free. However, due to its strong intermolecular crystallinity and intermolecular bonding, 100% PET virgin plastic is less likely to have plastic molecular groups fall off and become free after extraction. Therefore, the spectrum graph formed will also be different. As shown in Figures 5A-5C, it is a comparative spectrum overlay of another embodiment of the present invention.

[0137] like Figure 5A As shown, 10 mL of the PET sample solution and 10 mL of the 100% recycled PET material solution were taken, and 2 mL of the 4,4-bis(2-benzoxazolyl)stilbene (BBS) fluorescent dye was added respectively. After the reaction time was 15 minutes, the wavelength was set to 373 nm for excitation, and the spectral overlay of the difference in the position change of the double frequency wave at about the emission wavelength of 746 nm was observed. Figure 5AIt can be seen that since the molecules of the recycled PET in the 100% recycled PET material solution (NaOH-100% rPET / 0.05% BBS) are easily detached, its signal intensity is greater than that of the PET sample solution (NaOH-Virgin PET / 0.05% BBS).

[0138] Subsequent, such as Figure 5B As shown, 10 mL of the 10% sodium hydroxide solution, 10 mL of the PET sample solution, 10 mL of the blank solution (deionized water only) and 10 mL of the 100% recycled PET material solution were taken, and 2 mL of the 4,4-bis(2-benzoxazolyl)stilbene (BBS) fluorescent dye was added respectively. The reaction time was 15 minutes, and the wavelength was set to 373 nm for excitation. The spectral overlay of the difference in the position change of the double frequency wave at about the emission wavelength of 746 nm was observed. Figure 5B It can be seen that since the molecules of the recycled PET in the 100% recycled PET material solution (NaOH-100% rPET / 0.05% BBS) are easily detached, its signal intensity is greater than that of the PET sample solution (NaOH-Virgin PET / 0.05% BBS), and is also significantly different from 10 mL of the 10% sodium hydroxide solution (NaOH-Blank reagent / 0.05% BBS) and 10 mL of the blank solution (deionized water only, Deioned Water / 0.05% BBS).

[0139] To this end, after the fluorescence spectrum analysis, steps S95 and S96 are continued to analyze and compare the detection spectrum and the PET original spectrum (and simultaneously refer to the blank group spectrum, the alkaline solvent spectrum and the rPET spectrum). When the detection spectrum is not equal to the PET original spectrum, it is determined that the detection object contains a recycled PET.

[0140] However, in addition to the fluorescence spectrum analysis, color judgment analysis can also be performed, and after step S93, the following steps are further included:

[0141] Step S931: filtering the extraction liquid and the PET sample solution to form a test sample and a PET original sample;

[0142] Step S932: After drying the test sample and the PET original sample, the test color of the test sample and the PET color of the PET original sample are recorded respectively; and

[0143] Step S933: Compare the detection color and the PET color. When the detection color is different from the PET color, it is determined that the detection object contains recycled PET.

[0144] As shown in step S931, the extraction liquid and the PET sample solution are placed in a clean 250mL glass test tube (including a lid), and a glass funnel is placed on it to filter with a 0.45μm filter paper specification (at this time, the cleaned and drained 0.45μm filter paper is placed on a 100mL clean glass triangular pyramid bottle stand) to form a test sample and a PET original sample, and they are weighed separately.

[0145] Next, as shown in step S932, the test sample and the PET original sample are placed in a clean crucible for a drying process (the drying temperature is between 90° C. and 120° C. (preferably 110° C.), and the drying time is between 6 and 9 hours (preferably 8 hours)). After cooling, a test color of the test sample and a PET color of the PET original sample are recorded, and they are weighed again.

[0146] Finally, as shown in step S933, the detection color (when containing the recycled PET content, its color is between light yellow and khaki gray) and the PET color (which is between matte white and light grayish white) are compared. When the detection color is different from the PET color, it is determined that the detection object contains the recycled PET.

[0147] The present invention is based on the basic law of light absorption - Beer's law (Beer-Lambert law). When light passes through a solution, it will be affected by the high and low solute concentrations in the solution, which will affect the change in its transparent light. Therefore, when the solute concentration in the solution is high, the transparent light is low. Conversely, when the solute concentration in the solution is low, the transparent light is high, just as described by Beer-Lambert law.

[0148] As shown in step S933, when an alkaline solution is used as a solvent for sample extraction, the molecules of the recycled PET in the recycled plastic are more likely to fall off and become free than those of 100% PET virgin plastic, and are stably present in the solution. Since 100% PET virgin plastic has stronger intermolecular crystallinity and intermolecular bonding, it is less likely for the plastic molecular groups to fall off and become free after extraction.

[0149] On the contrary, the molecular groups of the recycled PET are more fragile. When an alkaline solution is used as a solvent for sample extraction, its molecular groups fall off more and become free. By comparing the changes in the color depth of the sample after extraction, it can be used to infer the amount of recycled PET added to the plastic. Beer's law is a general law applicable to uniform, non-scattering solutions.

[0150] In addition, the method of semi-quantitatively determining the plastic recycled material content of an article of the present invention is also referred to Figure 4 ,like Figure 4 As shown, after step S95, step S951 is further included: according to the difference ratio between the detection spectrum and the original PET spectrum, the content ratio of the recycled PET in the detection object is analyzed and obtained.

[0151] When an alkaline solution is used as a solvent for sample extraction, the molecules of recycled PET in the recycled plastic are more likely to fall off and become free than those of 100% PET virgin plastic, and exist stably in the solution.

[0152] Therefore, after extraction, the molecular groups of recycled PET will fall off more and become free. However, due to the strong intermolecular crystallinity and intermolecular bonding of 100% PET virgin plastic, it is less likely to cause the molecular groups of plastic to fall off and become free after extraction. Therefore, the spectra formed will also be different, and will vary depending on the content of the recycled PET.

[0153] See also Figure 5C ,like Figure 5C As shown, 10 mL of the 10% sodium hydroxide solution, 10 mL of the PET sample solution, 10 mL of the 50% recovery type PET material solution and 10 mL of the 100% recovery type PET material solution were taken, and 2 mL of the 4,4-bis(2-benzoxazolyl)stilbene (BBS) fluorescent dye was added respectively. After the reaction time was 15 minutes, the wavelength was set to 373 nm for excitation, and the difference in the position change of the double frequency wave at about the emission wavelength of 746 nm was observed. The spectrum overlay was obtained. Figure 5C It can be seen that since the molecules of the recycled PET in the 100% recycled PET material solution (NaOH-100% rPET / 0.05% BBS) are easily detached, its signal intensity is greater than that of the PET sample solution, and although the molecules of the recycled PET in the 50% recycled PET material solution (NaOH-50% rPET / 0.05% BBS) are also detached, the detachment amount is less than that of the 100% recycled PET material solution, so its signal intensity is between the 100% recycled PET material solution and the PET sample solution (NaOH-Virgin PET / 0.05% BBS), and is also greater than the signal intensity of 10mL of the 10% sodium hydroxide solution (NaOH-Blank reagent / 0.05% BBS).

[0154] Depend on Figure 5CIt can be seen that the present invention can analyze and obtain the content ratio of the recycled PET in the detected object by using the difference ratio between the detected spectrum and the original PET spectrum.

[0155] To this end, the present invention utilizes the difference in strength of the bond between molecules, and adds appropriate fluorescent dyes dispersed in a continuous matrix. When the concentration of the fluorescent dye increases, its formation energy aggregates with the detached recycled plastic molecular groups, the excitation wavelength is set at 373nm, and the instrument fluorescence intensity value of the 746nm double frequency wave is observed. From the above practical example, it is found that the double frequency wave of the excitation light source can show that there is a significant difference in strength between the scattered waves of the original plastic and the recycled plastic, which can be used as a qualitative method to detect whether an item contains plastic recycled materials (recycled plastics), and a rapid semi-quantitative method using the strength difference ratio.

[0156] The order of execution of each step in the above embodiment does not mean the order of execution. The order of execution of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiment of the present application.

[0157] The above is only a preferred embodiment of the present invention and is not intended to limit the scope of the present invention. All equivalent changes and modifications to the shape, structure, characteristics and spirit described in the claims of the present invention should be included in the scope of the claims of the present invention.

Claims

1. A method for detecting whether an article contains plastic recycling materials, characterized in that: The method uses a first detection part, a second detection part and a third detection part of an object to perform detection, and the steps include: Detecting a basic yellowing index of the first detection portion through a color difference measuring device; irradiating the first detection portion with a first light source; The color difference measuring device detects the first detection part to obtain a yellowing index, and obtains a yellowing index of the first detection part according to the yellowing index and the basic yellowing index; Capturing a first surface image of the second detection portion through an image capturing device; Within a total detection time, spraying a water mist on the second detection part and then irradiating a second light source; capturing a second surface image of the second detection portion through the image capturing device; The third detection part is placed in a detection chamber of a thermogravimetric analysis device, and the third detection part generates a thermogravimetric change in the detection chamber; The thermogravimetric analysis device analyzes and calculates according to the thermogravimetric change to obtain an activation energy value; comparing the yellowing index with a standard yellowing index of a standard object, a first defect state of the first surface image with a second defect state of the second surface image, and the activation energy value with a standard activation energy value of a standard object; and When the yellowing index is less than the standard yellowing index, the second defect state is greater than the first defect state, and the activation energy value is less than the standard activation energy value, it is determined that the article contains part of the plastic recycled material.

2. The method for detecting whether an article contains plastic recycled materials according to claim 1, characterized in that: In the step of irradiating the first detection portion with a first light source, the first light source is a UV light source, a xenon arc light source, a carbon arc light source or a mercury lamp source.

3. The method for detecting whether an article contains plastic recycled materials according to claim 2, characterized in that: The UV light source is between 200nm and 400nm.

4. The method for detecting whether an article contains plastic recycled materials according to claim 3, characterized in that: Before the step of detecting a basic yellowing index of the first detection part through a color difference measuring device, the method includes the following steps: Take a standard object and use the color difference measuring device to measure and obtain a first yellowing index; After irradiating the standard article with the first light source, detecting and obtaining a second yellowing index of the standard article by the color difference measuring device; and Obtaining a standard yellowing index according to the second yellowing index and the first yellowing index; The standard article is an article that does not contain recycled plastic material.

5. The method for detecting whether an article contains plastic recycled materials according to claim 4, characterized in that: The step of irradiating the first detection portion with a first light source includes the following steps: The first light source illuminates the first detection portion according to an illumination time, wherein the illumination time is between 24 hours and 450 hours.

6. The method for detecting whether an article contains plastic recycled materials according to claim 1, characterized in that: In the step of spraying water on the second detection part and irradiating a second light source within a total detection time, the second light source uses a UV light source, a xenon arc light source, a carbon arc light source or a mercury lamp source.

7. The method for detecting whether an article contains plastic recycled materials according to claim 6, characterized in that: The step of spraying water on the second detection part and then irradiating a second light source within a total detection time includes the steps of: In a first time interval, using the second light source to illuminate a surface of the second detection portion, wherein the surface has a first temperature between 50 and 80° C.; and Spraying the water mist onto the second detection portion within a second time interval, wherein the second light source is turned off when spraying the water mist; The first time interval and the second time interval are repeatedly executed in the total detection time.

8. The method for detecting whether an article contains plastic recycled materials according to claim 7, characterized in that: In the step of using the second light source to illuminate a surface of the second detection portion within a first time interval, the first time is between 85 and 150 minutes.

9. The method for detecting whether an article contains plastic recycled materials according to claim 7, characterized in that: In the step of spraying the water mist onto the second detection portion and irradiating the second light source within a second time, the second time is between 5 and 60 minutes.

10. The method for detecting whether an article contains plastic recycled materials according to claim 1, characterized in that: Before the step of placing the third detection part in a detection chamber of a thermogravimetric analysis device and causing the third detection part to produce a thermogravimetric change in the detection chamber, the method comprises the following steps: Taking a standard object and placing it in the detection chamber, and adjusting a chamber temperature of the detection chamber so that the standard object generates a standard thermogravimetric change in the detection chamber; and The thermogravimetric analysis device analyzes and calculates according to the standard thermogravimetric change to obtain a standard activation energy value; The chamber temperature is between 20 and 1000°C.

11. The method for detecting whether an article contains plastic recycled materials according to claim 1, characterized in that: The step of obtaining an activation energy value by analyzing and calculating the thermogravimetric change using the thermogravimetric analysis device comprises the following steps: Adjusting a chamber temperature of the detection chamber, wherein the chamber temperature is between 20 and 1000° C.; and The thermogravimetric analysis device obtains the thermogravimetric change of the third detection portion through a temperature change of the chamber temperature.

12. The method for detecting whether an article contains plastic recycled materials according to claim 1, characterized in that: The article is composed of the plastic recycled material and / or a non-plastic recycled material, and further, the plastic recycled material and the non-plastic recycled material are selected from one of polyethylene, polypropylene, polyethylene terephthalate, polycarbonate, polycarbonate and acrylonitrile butadiene styrene copolymer, polystyrene or polycarbonate and acrylonitrile butadiene styrene copolymer, and thermoplastic polyurethane.

13. A method for detecting whether an article contains plastic recycling materials, characterized in that: The steps include: Take a test object and put it into a glass beaker; A sodium hydroxide solution is added to the glass beaker, and then covered with a watch glass cover and subjected to an extraction process to form an extraction sample; Taking deionized water to rinse the glass beaker and the extraction sample on the watch glass cover to form an extraction liquid; After adding 4,4-bis(2-benzoxazolyl) to the extraction liquid and a PET sample solution respectively, a fluorescence spectrum analysis is performed under an analysis condition to obtain a detection spectrum and a PET original spectrum; Analyze and compare the detected spectrum and the PET original spectrum; and When the detected spectrum is not equal to the original spectrum of the PET, it is determined that the detected object contains a recycled PET.

14. The method for detecting whether an article contains plastic recycled materials according to claim 13, characterized in that: Before the step of taking a test object and putting it into a glass beaker, the test object is pre-processed in advance, and the pre-processing is to cut the test object into a size of 1 cm x 1 cm.

15. The method for detecting whether an article contains plastic recycled materials according to claim 14, characterized in that: In the step of adding a sodium hydroxide solution into the glass beaker and covering it with a watch glass cover to perform an extraction treatment, the temperature of the extraction treatment is between 105° C. and 125° C., and the time of the extraction treatment is between 70 and 100 minutes.

16. The method for detecting whether an article contains plastic recycled materials according to claim 15, characterized in that: After adding 4,4-bis(2-benzoxazolyl) to the extraction liquid and a PET sample solution respectively, a fluorescence spectrum analysis is performed under an analysis condition, wherein the analysis condition is that the excitation wavelength is set at 373nm, the incident slit is set at 5nm, the emission slit is set at 5nm, the wavelength scanning range is set between 360nm and 800nm, and the scanning rate is within 120nm / min.

17. The method for detecting whether an article contains plastic recycled materials according to claim 16, characterized in that: After the step of taking deionized water to rinse the glass beaker and the extraction sample on the watch glass cover to form an extraction liquid, the method further comprises the following steps: filtering the extraction liquid and the PET sample solution to form a test sample and a PET original sample; After drying the test sample and the PET original sample, respectively, a test color of the test sample and a PET color of the PET original sample are recorded; and The detection color is compared with the color of the PET. When the detection color is different from the color of the PET, it is determined that the detection object contains a recycled PET.

18. The method for semi-quantifying the plastic recycled material content of an article according to claim 17, characterized in that: In the step of drying the test sample and the PET original sample respectively, the drying temperature is between 90° C. and 120° C., and the drying time is between 6 and 9 hours.

19. A method for semi-quantifying the plastic recycled material content of an article, characterized in that: The steps include: Take a test object and put it into a glass beaker; A sodium hydroxide solution is added to the glass beaker, and then covered with a watch glass cover and subjected to an extraction process to form an extraction sample; Taking deionized water to rinse the glass beaker and the extraction sample on the watch glass cover to form an extraction liquid; After adding 4,4-bis(2-benzoxazolyl) to the extraction liquid and a PET sample solution respectively, a fluorescence spectrum analysis is performed under an analysis condition to obtain a detection spectrum and a PET original spectrum; Analyze and compare the detected spectrum and the PET original spectrum; and According to the difference ratio between the detected spectrum and the original spectrum of PET, the content ratio of the recycled PET in the detected object is analyzed and obtained.

20. The method for semi-quantifying the plastic recycled material content of an article according to claim 19, characterized in that: Before the step of taking a test object and putting it into a glass beaker, the test object is pre-processed in advance, and the pre-processing is to cut the test object into a size of 1 cm x 1 cm.

21. The method for semi-quantifying the plastic recycled material content of an article according to claim 20, characterized in that: In the step of adding a sodium hydroxide solution into the glass beaker and covering it with a watch glass cover to perform an extraction treatment, the temperature of the extraction treatment is between 105° C. and 125° C., and the time of the extraction treatment is between 70 and 100 minutes.

22. The method for semi-quantifying the plastic recycled material content of an article according to claim 21, characterized in that: After adding 4,4-bis(2-benzoxazolyl) to the extraction liquid and a PET sample solution respectively, a fluorescence spectrum analysis is performed under an analysis condition, wherein the analysis condition is that the excitation wavelength is set at 373nm, the incident slit is set at 5nm, the emission slit is set at 5nm, the wavelength scanning range is set between 360nm and 800nm, and the scanning rate is within 120nm / min.